Mechanical elongation of astrocyte processes to create living scaffolds for nervous system regeneration. (7th June 2016) - Katiyar, Kritika S.; Winter, Carla C.; Struzyna, Laura A.; Harris, James P.; Cullen, D. Kacy
Abstract: Following brain injury or neurodegenerative disease, successful regeneration requires orchestrated migration of neurons and reformation of long‐distance communication fibres, or axons. Such extensive regeneration does not occur in the mature brain; however, during embryonic development, pathways formed by glial cells extend several millimeters (mm) to create 'living scaffolds' for targeted neural cell migration and axonal pathfinding. Techniques to recapitulate long process outgrowth in glial cells have proven elusive, preventing the exploitation of this developmental mechanism for regeneration. In the current study, astrocytes were induced to form a network of interconnected processes that were subjected to controlled mechanical tension in vitro using custom‐built mechanobioreactors. We discovered a specific micron (μm)‐scale mechanical growth regime that induced elongation of the astrocytic processes to a remarkable length of 2.5 mm at an optimal rate of 12.5 μm/h. More rapid mechanical regimes (> 20 μm/h) caused greater incidence of process degeneration or outright breakage, whereas slow regimes (< 4 μm/h) led to adaptive motility, thus failing to achieve process elongation. Cellular phenotype for this astrocytic 'stretch‐growth' was confirmed based on presentation of the intermediate filament glial fibrillary acidic protein (GFAP). Mechanical elongation resulted in the formation of dense bundles of aligned astrocytic processes. Importantly, seeded neurons readily adhered to, and extended neurites directly along, the elongated astrocytic processes, demonstrating permissiveness to support neuronal growth. This is the first demonstration of the controlled application of mechanical forces to create long astrocytic processes, which may form the backbone of tissue‐engineered 'living scaffolds' that structurally emulate radial glia to facilitate neuroregeneration. Copyright © 2016 John Wiley & Sons, Ltd.